Modification of the properties of porous silicon for solar cells by hydrogenation - Єрохов, Валерій Юрійович; Дружинін, Анатолій Олександрович; Єрохова, Ольга Валерієвна (Eastern-European Journal of Enterprise Technologies, 2015)
The prospects of creating a solar cell with antireflection coating on porous silicon were shown, for which the process of electrochemical hydrogenation of porous silicon on p-type silicon substrates with a resistivity of 0.1...10 Om×sm and substrates with the formed emitter junction n+-p was studied. For the process of electrochemical hydrogenation of porous silicon at its cathodic polarization, potentiostatic current-voltage curves of the system Pt (anode) - electrolyte - «porous silicon/silicon» (cathode) for electrolytes with different chemical composition were studied. A comparison of the photoluminescence spectra of as-grown, chemically processed and hydrogenated porous layers has shown that hydrogen saturation of the porous silicon surface during cathodic polarization increases photoluminescence intensity to a level typical for samples that previously have passed special chemical treatment. The research results of luminescent properties of hydrogenated porous silicon layers can be interpreted by an increase in photoluminescence intensity of hydrogenated porous silicon layers. These results are confirmed by experiments on the secondary ion mass spectrometer (SIMS), where, after hydrogenation, we can see a steady intensity (number of the read pulses) of secondary ions of the multicrystalline Baysix type silicon substrate surface in static mode with the presence of H2+ ions. Through the model representation of the silicon PEC structure with the antireflection coating based on the porous silicon layer, the solar cell was developed and its parameters, which have shown that the conversion efficiency of the SC with hydrogenated porous silicon is by 1.28 times higher (16.1%) than without it (12 6%) were measured.